Infection of Soil-Transmitted Helminth among Mining Workers in Southeast Sulawesi - Amraeni, Yunita; Nirwan, Muhammad; Suwardi, Jumintono (Al-Sihah: The Public Health Science Journal, 2022)
Soil-Transmitted Helminth (hereafter STH) is considered as the leading cause of global health problems. This study aims to know the intensity and prevalence of STH infections among mining workers by comparing fecal and nail examinations in Morindino Village, Kambowa District, North Buton Regency Southeast Sulawesi Province. Feces were examined by using a native method, whilst the nails were observed by a sediment method. Additionally, descriptive and inferential analysis with independent t-tests were used to analyze the data. A total of 48 respondents were involved in this study. The observations of fecal respondents indicated that 4 (8.3%) of the respondents were infected with Ascaris lumbricoides, 12 (25%) had hookworm eggs, and 32 respondents (66.67%) were not infected. Moreover, the observation of STH worm eggs using nail samples showed that 1 respondent (2%) was infected with Ascaris lumbricoides, 4 (8.3%) respondents were infected by hookworm, and 43 respondents (89.58%) were free. The intensity of the attack was still in the mild category for all types of worm eggs; yet the highest attack was on hookworm for both examinations (2.16 and 2.25 eggs/individual). The research site took place around a sand mining land area with loose sandy soil structures that are protected from sunlight and mixed with humus to support the STH life cycle. Some individuals did open defecation habits at the research site leads to the STH contamination of the soil. Thus, the surveillance programs and infections control should be effectively implemented to manage worms incident.